Global Change Modulates Microbial Carbon Use Efficiency: Mechanisms and Impacts on Soil Organic Carbon Dynamics - Jingwei Shi; Lei Deng; Jianzhao Wu; Yuanyuan Huang; Yajing Dong; Josep Peñuelas; Yang Liao; Lin Yang; Xingyun Huang; Hailong Zhang; Jiwei Li; Zhouping Shangguan; et al. (Global Change Biology, 2025)
Microbial carbon use efficiency (CUE) is a key parameter of initial microbial utilization of organic matter in soil. The responses of CUE to global change factors (GCFs) remain unclear due to their multiple effects and interactions. Here, this study generalized 385 observations obtained using various methods, including 13 C‐/ 14 C‐labeled substrates, 18 O‐labeled water, stoichiometric modeling, and others. The effects of climate change (drought, precipitation, warming), fertilization (nitrogen addition, phosphorus addition, potassium addition, and nitrogen fertilization combined with phosphorus and potassium), land use conversion, and natural restoration, were evaluated along with their 16 associated GCFs on CUE. CUE was insensitive to climate change factors and most fertilization practices, maintaining a mean value of 0.36 under global change scenarios. Farmland conversion to forest and vegetation restoration decreased CUE by 11% and 17%, respectively. Grassland restoration increased CUE by 41%, indicating that grasslands have high potential for soil carbon accrual. Nitrogen fertilization combined with phosphorus and potassium increased CUE by 18% because the combined application of nutrients allows plants to produce organic matter sources with high‐quality and decreases nutrient limitations for microorganisms. Increase in soil pH induced by GCFs leads to higher CUE. The CUE was decoupled from soil organic carbon content under several global change scenarios (e.g., warming, fertilization), suggesting that this relationship is not universally consistent across GCFs. This study provides a new perspective on the responses of CUE to GCFs and deepens our understanding of the global change effects on microbial physiology with consequences for soil carbon cycling.